The financial milieu of the IASB and AASB - Brown, Alistair (CPA, 2006)
This paper considers the implications of the convergence of the accounting standards of the International Accounting Standards Board with those of the Australian Accounting Standard Board. Australia seems well placed to comply with the international accounting standards in 2005, but not quite in the way the boards would have us imagine. While actively seeking funds from large multinational corporations and elite accounting firms, the AASB is dominated by stakeholder groups with what are described as “corefinancial” and “partial-financial” interests. This financial milieu may offer cosy deals for the key stakeholders, but does little in the way of civic responsibilities and accounting service for the wider public.